Integrated metabolite profiling and in silico screening reveal the cholesterol‐modulating potential of tauco, an Indonesian fermented soybean paste - Nabillah, Salfa Athallah Agtari; Wati, Roidah Cahya; Nurmilah, Siti; Fitrianto, Nur; Ningsih, Dian Riana; Frediansyah, Andri (Universitas Gadjah Mada, 2026)
Tauco, a traditional Indonesian fermented soybean paste, is a promising yet under‐characterized source of dietary bioactives. To systematically evaluate its functional potential, we first identified ultrasonic‐assisted extraction (UAE) as the most efficient method, yielding the highest total phenolic content (28.70 mg GAE/g) and the strongest in vitro antioxidant activity (ABTS IC50 = 0.238 mg/mL). Untargeted LC–HRMS‐based metabolite profiling of this optimal extract revealed a diverse phytochemical profile rich in isoflavone aglycones, sterols, and specialized lipids. To link this chemical inventory to a specific health‐related mechanism, we performed molecular docking against HMG‐CoA reductase (HMGR), the rate‐limiting enzyme in cholesterol biosynthesis. This in silico screening prioritized the triterpenoid uvaol and the phytosterol stigmasterol as top‐binding candidates, with predicted binding affinities stronger than the reference ligand (−8.2 and −7.6 kcal/mol respectively). Overall, our integrated approach shows that UAE efficiently recovers a complex mixture of antioxidants from tauco and identifies specific metabolites with high predicted affinity for a key cardiometabolic target, providing a mechanistic hypothesis for its functional benefits and prioritizing lead compounds for future validation.